IFPRI Malawi Monthly Maize Market Report, July 2025 - International Food Policy Research Institute; Benson, Anderson (International Food Policy Research Institute, 2025)
Highlights Retail prices of maize increased on average by 13 percent in July. Prices rose in all monitored markets across all regions of Malawi despite continued imports. Prices rose most steeply in the Southern region, increasing interregional differences.